Step
*
1
of Lemma
rv-between-translation
1. n : ℕ
2. a : ℝ^n
3. b : ℝ^n
4. c : ℝ^n
5. z : ℝ^n
6. z + a ≠ z + c
7. t : ℝ
8. t ∈ (r0, r1)
9. ∀i:ℕn. ((z + b i) = (t*z + a + r1 - t*z + c i))
10. i : ℕn
11. ((z i) + (b i)) = ((t * ((z i) + (a i))) + ((r1 - t) * ((z i) + (c i))))
⊢ (b i) = ((t * (a i)) + ((r1 - t) * (c i)))
BY
{ (nRAdd ⌜-(z i)⌝ (-1)⋅ THEN Auto) }
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  a  :  \mBbbR{}\^{}n
3.  b  :  \mBbbR{}\^{}n
4.  c  :  \mBbbR{}\^{}n
5.  z  :  \mBbbR{}\^{}n
6.  z  +  a  \mneq{}  z  +  c
7.  t  :  \mBbbR{}
8.  t  \mmember{}  (r0,  r1)
9.  \mforall{}i:\mBbbN{}n.  ((z  +  b  i)  =  (t*z  +  a  +  r1  -  t*z  +  c  i))
10.  i  :  \mBbbN{}n
11.  ((z  i)  +  (b  i))  =  ((t  *  ((z  i)  +  (a  i)))  +  ((r1  -  t)  *  ((z  i)  +  (c  i))))
\mvdash{}  (b  i)  =  ((t  *  (a  i))  +  ((r1  -  t)  *  (c  i)))
By
Latex:
(nRAdd  \mkleeneopen{}-(z  i)\mkleeneclose{}  (-1)\mcdot{}  THEN  Auto)
Home
Index